Rethinking Guidelines for VTE Risk Among Nursing Home Residents: A Population-Based Study Merging Medical Record Detail With Standardized Nursing Home Assessments - Leibson, Cynthia L. (American College of Chest Physicians, 2014)
BACKGROUND: Nursing home (NH) residents are at increased risk for both VTE and bleeding from pharmacologic prophylaxis. Construction of prophylaxis guidelines is hampered by NH-specific limitations with VTE case identification and characterization of risk. We addressed these limitations by merging detailed provider-linked Rochester Epidemiology Project (REP) medical records with Centers for Medicare and Medicaid Services Minimum Data Set (MDS) NH assessments. METHODS: This population-based nested case-control study identified all Olmsted County, Minnesota, residents with first-lifetime VTE October 1, 1998, through December 31, 2005, while a resident of an NH (N = 91) and one to two age-, sex-, and calendar year-matched NH non-VTE control subjects. For each NH case without hospitalization 3 months before VTE (n = 23), we additionally identified three to four nonhospitalized NH control subjects. REP and MDS records were reviewed before index date (VTE date for cases; respective REP encounter date for control subjects) for numerous characteristics previously associated with VTE in non-NH populations. Data were modeled using conditional logistic regression. RESULTS: The multivariate model consisting of all cases and control subjects identified only three characteristics independently associated with VTE: respiratory infection vs no infection (OR, 5.9; 95% CI, 2.6-13.1), extensive or total assistance with walking in room (5.6, 2.5-12.6), and general surgery (3.3, 1.0-10.8). In analyses limited to nonhospitalized cases and control subjects, only nonrespiratory infection vs no infection was independently associated with VTE (8.8, 2.7-29.2). CONCLUSIONS: Contrary to previous assumptions, most VTE risk factors identified in non-NH populations do not apply to the NH population. NH residents with infection, substantial mobility limitations, or recent general surgery should be considered potential candidates for VTE prophylaxis.